Decavanadate toxicology and pharmacological activities: V10 or V1, both or none? - Aureliano, M. (2016)
This review covers recent advances in the understanding of decavanadate toxicology and pharmacological applications. Toxicological in vivo studies point out that V10 induces several changes in several oxidative stress parameters, different from the ones observed for vanadate (V1). In in vitro studies with mitochondria, a particularly potent V10 effect, in comparison with V1, was observed in the mitochondrial depolarization (IC50 = 40 nM) and oxygen consumption (99 nM). It is suggested that mitochondrial membrane depolarization is a key event in decavanadate induction of necrotic cardiomyocytes death. Furthermore, only decavanadate species and not V1 potently inhibited myosin ATPase activity stimulated by actin (IC50 = 0.75 M) whereas exhibiting lower inhibition activities for Ca2+-ATPase activity (15 M) and actin polymerization (17 M). Because both calcium pump and actin decavanadate interactions lead to its stabilization, it is likely that V10 interacts at specific locations with these proteins that protect against hydrolysis but, on the other hand, it may induce V10 reduction to oxidovanadium(IV). Putting it alltogether, it is suggested that the pharmacological applications of V10 species and compounds whose mechanism of action is still tobe clarified might involve besides V10 and V1 also vanadium(IV) species.